Tea: quality pays dividends - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2006)
It is hard for tea producers to reverse the decline in world prices. But improving quality and highlighting the marketing appeal of locally grown teas could help the best varieties to stand out from the rest...